Regulation of an expiry period of preventive prison in the procedural stages and its impact on the due process guarantee - Hurtado Niño de Guzmán, Edison Wilber (2021)
Preventive detention as a measure of procedural coercion of a personal nature turns out to be the most harmful because its application affects the deprivation of liberty of the accused, who enjoys the guarantee of the presumption of innocence. The unnecessary prolongation of the same violates the right of the accused to a trial within a reasonable time, even more so when the accused is deprived of his freedom. In this work, the author analyzes the lack of regulation of the expiration date of the procedural measure by procedural stage and tests a possible solution that involves a normative proposal to regulate the expiration period of said  precautionary measure in a clear guarantee of the right to be subjected to a trial without undue delay.